Initial acoustic assessment of long underground enclosures for designers. (November 2020) - Nowicka, E.
Highlights: The acoustic quality of public space is determined by the speech sounds reception. An index-based method is proposes for assessing the acoustic quality of long spaces. Method is intended to serve as a preliminary analysis at the design stage. Method increase the safety and comfort for users. Method allow to reduce the cost of further acoustic adaptations. Abstract: The acoustic quality of long spaces is often a problem confronting the designer. Ensuring adequate speech reception in relation to sound alarm systems in such spaces is one of the key factors determining the acoustic quality of a space. The aim of this paper is to present an initial, index-based method for the assessment of the acoustic quality of long spaces during the design process, taking into account selected architectural and acoustic parameters. The development of the method is based on acoustic testing, which was carried out in a number of subway stations. The acoustic quality of long spaces is determined by speech intelligibility, which is mainly influenced by reverberation time within an enclosure. This is why testing was focussed on reverberation time and speech intelligibility. The enclosures were selected according to a variety of cross-sectional shapes and acoustic absorption characteristics. The presented method is expected to provide an easy-to-use assessment of long spaces designed in terms of speech intelligibility, as required for sound alarm systems, conforming among other things, to applicable standards. By applying this method, it is possible to increase the safety of long enclosures' occupants and reduce or avoid costs associated with improving the acoustic conditions of ready-to-use long enclosures.